Meningkatkan Kemampuan Menulis Siswa dalam Konteks Bahasa Inggris sebagai Bahasa Penutur Asing - Maryani, Ade Irma (Universitas Siliwangi, 2025)
This study aims to examine the improvement of writing skills in a junior high school student at a school in Pangandaran through the use of images and writing guidance. This research employed an action research method with a single female student as the data source. Data were collected from observations and interviews, which were transcribed and analyzed using thematic analysis. The findings of this study indicate that writing guidance can enhance the student's ability to acquire new vocabulary and improve grammatical structure. Additionally, the use of images positively influenced the student’s ability to generate ideas and organize her writing more effectively. Based on these results, the use of images combined with writing guidance is effective in supporting the writing learning process for junior high school students in one of the schools in Pangandaran.